2018
DOI: 10.1002/adma.201801821
|View full text |Cite
|
Sign up to set email alerts
|

Moving Droplets in 3D Using Light

Abstract: The emulation of the complex cellular and bacterial vesicles used to transport materials through fluids has the potential to add revolutionary capabilities to fluidic platforms. Although a number of artificial motile vesicles or microdroplets have been demonstrated previously, control over their movement in liquid in 3D has not been achieved. Here it is shown that by adding a chemical "fuel," a photoactive material, to the droplet, it can be moved in any direction (3D) in water using simple light sources witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 35 publications
(45 reference statements)
2
94
1
Order By: Relevance
“…Xiao et al. showed that by adding a chemical “fuel,” a photoactive material, to the droplet, can move in any direction in water using simple light sources [47] …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Xiao et al. showed that by adding a chemical “fuel,” a photoactive material, to the droplet, can move in any direction in water using simple light sources [47] …”
Section: Figurementioning
confidence: 99%
“…Fe 2 O 3 nanoparticles were synthesized by hydrothermal method. The detailed procedures were shown in Figure 4a [47, 48] . As shown in Figure 4a, firstly, 90 mL NaOH solution (6 M) was added dropwise into 100 mL FeCl 3 solution (2 M) under magnetic stirring.…”
Section: Figurementioning
confidence: 99%
“…The development of motile cell-mimetic compartmentalised systems is receiving increasing interest due to their potential in applications including targeted drug delivery 1,2,3 and environmental restoration 4,5 . The fact that controlled motility and chemotaxis is a behaviour that is considered to be one of the hallmarks of life has also made it a focus in the endeavour to construct artificial cells that mimic biological cells in form and function 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…To propel an object, various strategies have been exploited such as bubble-propulsion 8,9,10 , diffusiophoresis 11,12,13,14,15 , magnetic force 16,17 , and the Marangoni effect 18,19,20 . Among these methods, the Marangoni effect is a commonly used way to induce motion since it can be easily achieved 3 . The asymmetric distribution of interfacial tension (IFT) around a droplet spontaneously generates a Marangoni flow on the droplet surface, driving its motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation